2015
DOI: 10.5423/ppj.oa.03.2015.0027
|View full text |Cite
|
Sign up to set email alerts
|

Application of Volatile Antifungal Plant Essential Oils for Controlling Pepper Fruit Anthracnose by Colletotrichum gloeosporioides

Abstract: Anthracnose caused by Colletotrichum gloeosporioides has been destructive during pepper fruit production in outdoor fields in Korea. In vitro antifungal activities of 15 different plant essential oils or its components were evaluated during conidial germination and mycelial growth of C. gloeosporioides. In vitro conidial germination was most drastically inhibited by vapour treatments with carvacrol, cinnamon oil, trans-cinnamaldehyde, citral, p-cymene and linalool. Inhibition of the mycelial growth by indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 52 publications
(54 reference statements)
4
49
0
3
Order By: Relevance
“…Recently, Hong et al. () showed that clove oil can protect green pepper fruit from anthracnose cause by Colletotrichum gloesporioides . Moreover, Nana et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hong et al. () showed that clove oil can protect green pepper fruit from anthracnose cause by Colletotrichum gloesporioides . Moreover, Nana et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sirirat and Kittipot (2010) showed that clove oil can prevent the postharvest rot of tomato and suggested that this effectiveness could be linked to the inhibition of fungal conidia germination. Recently, Hong et al (2015) showed that clove oil can protect green pepper fruit from anthracnose cause by Colletotrichum gloesporioides. Moreover, Nana et al (2015) also showed the in vivo effectiveness of clove oil to protect cocoa pod against black pod disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Hong et al reported that trans-cinnamaldehyde not only drastically inhibited the spore germination and mycelial growth of Colletotrichum gloeosporioides, which is the causal agent of anthracnose in pepper fruit, but also reduced the lesion diameter on C. gloeosporioides-inoculated immature green pepper fruit. 16 In our recent study, CA was demonstrated to be able to inhibit the mycelial growth of G. citri-aurantii and induced defence responses against sour rot in citrus fruit. 17 In addition, it was found to be effective in inhibiting aerobic, psychrophilic, yeast and mould growth on fresh-cut papaya and on fresh-cut watermelon.…”
Section: Introductionmentioning
confidence: 92%
“…T. D. Kodituwakku, K. Abeywickrama and K. O. L. C. Karunanayake Taking the pathological, physicochemical and sensory properties of mangoes subjected to essential oil treatments into consideration, cinnamon bark oil treatments could be developed for commercial application in order to introduce mango fruits to the market with a better postharvest quality. Cinnamaldehyde, which has been identifi ed as the major component in cinnamon bark oil (Kodituwakku, 2018) has been confi rmed to be an antifungal compound in many studies (Hong et al, 2015;Marei and Abdelgalei, 2018). Few other components including eugenol and caryophyllene were detected as minor compounds in smaller quantities in addition to cinnamaldehyde.…”
Section: Sensory Propertiesmentioning
confidence: 99%